Fantastic Mr. Fox [videorecording (DVD)] - Anderson, Wes, 1969-; Clooney, George; Streep, Meryl; Schwartzman, Jason, 1980-; Murray, Bill, 1950 September 21-; Wilson, Owen, 1968-; Desplat, Alexandre; Dahl, Roald (20th Century Fox Home Entertainment, 2010)
Mr. and Mrs. Fox live a happy home life underground with their eccentric son Ash. Mr. Fox works as a journalist, but against the advice of Badger, his attorney, he moves his family into a larger and finer home inside a tree on a hill. The treehouse has an excellent view of the nearby farms of Boggis, Bunce, and Bean. Ash becomes hostile when his cousin, Kristofferson, joins the family for an extended stay. Mr. Fox decides to raid the farms, but this leads the farmers to stakeout the treehouse. The farmers try to dig the Fox family out, but they dig even faster. Mr. Fox organizes a tunneling project to burrow under all three farms and steal all the chickens, ducks, geese and turkeys.